The resilience of parents and carers who administer medicines to children at home: a qualitative systematic review protocol - Stephen Morris; Simon Pini; Beth Fylan; Franki Wilson; Helen Faulkner; David P. Alldred (Systematic Reviews)
Abstract Background Parents and carers are increasingly expected to administer prescribed medicines to their children at home. However, parents and carers are not always able to administer medicines as directed by the prescriber and ultimately must rely on their own judgment to administer medicines safely. This process is often unseen but may contain important learning for professionals, academics, and wider society. Studying safety in everyday healthcare work presents researchers with many challenges. However, recent developments in our understanding of resilience and how it manifests within healthcare can provide an effective framework for enquiry. The aim of this review is to use resilience theory to explore parents’ and carers’ experiences when administering medicines to children at home. Methods This systematic review will follow the framework synthesis method. An iterative search strategy, using a scoping search of the major databases (Embase, PyscINFO, CINAHL, Cochrane and PubMed) will be used. The three main search terms are parents and carers, administration of medicines, and the home environment. Included studies will contain qualitative data and investigate the experiences of parents or carers who administer prescribed medicines to children at home. Relevant studies will be quality assessed using the Joanna Briggs Institute critical appraisal checklist for qualitative research. Framework synthesis will be completed by following five stages: familiarisation, thematic framework identification, indexing, charting, mapping, and interpretation. The findings identified in the data extraction phase will be indexed and charted according to the three elements of Moments of Resilience theory. Discussion This protocol describes a novel method to address an important patient safety issue. A strength of this review will be not only to identify, describe and collate existing studies, but also to learn about the application of resilience theory to a medication safety topic. The knowledge generated from this will inform intervention development to improve the support for families to administer medicines safely at home. Systematic review registration This review has been registered on the International Prospective Register of Systematic Reviews database (PROSPERO) #487154.